(untitled) (Journal of International Studies, 2024)
Territorial disputes frequently emerge in the wake of new nationstates asserting their sovereignty and expanding their influence. These claims often hinge on the nebulous grounds of historical entitlement and legal precedent. Sixteen years post-independence from the United States, the Philippines formally staked a claim to Sabah in 1962, a move initiated under President Diosdado Macapagal and escalated by the more assertive policies of President Ferdinand Marcos. The main objective of this article is to explore the degree to which socioeconomic cooperation has played a role in rejuvenating and bolstering the Philippines’ foreign relations with Malaysia amidst the Sabah dispute. This historical analysis utilises qualitative methodologies to scrutinise primary and secondary sources, encompassing official records and documents pertinent to the dispute over the Philippines’ claim to Sabah. Despite the long-standing and potentially destabilising territorial dispute over Sabah, the Philippines and Malaysia transitioned from confrontation to collaboration, leading to robust socio-economic ties and increased regional stability within ASEAN. The problem lies in understanding how this diplomatic shift occurred, the strategies employed by the administrations of Presidents Aquino and Ramos in redirecting the focus from territorial claims to mutual economic growth, and the implications of this shift for both the bilateral relationship and the broader ASEAN dynamics. The findings indicate that, in contrast to the approaches of Presidents Diosdado Macapagal and Ferdinand Marcos, Presidents Corazon Aquino and Fidel V. Ramos skilfully shifted the focus from the Sabah issue to fostering robust socio-economic collaboration. This pivot served as a critical turning point, establishing the foundation for a comprehensive, multi-layered cooperation that is free from the constraints of the Sabah dispute.